2004
DOI: 10.1097/01.ccm.0000133332.48386.85
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase inhibition in acute lung injury: Results of the STRIVE study

Abstract: Intravenous sivelestat had no effect on 28-day all-cause mortality or ventilator-free days in a heterogeneous acute lung injury patient population managed with low tidal volume mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
242
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(247 citation statements)
references
References 12 publications
1
242
2
2
Order By: Relevance
“…However, a subsequent multinational randomized double-blinded trial did not demonstrate the improvement in both short-term (28 days) and long-term (180 days) mortality (21). As a result, most countries have not approved sivelestat and it is not used for the treatment of ALI/ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a subsequent multinational randomized double-blinded trial did not demonstrate the improvement in both short-term (28 days) and long-term (180 days) mortality (21). As a result, most countries have not approved sivelestat and it is not used for the treatment of ALI/ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…3). Predetermined sub-group analysis on studies conducted in Japan only, by excluding one study by Zeiher et al (21), again demonstrated no benefit of sivelestat on short term mortality (RR 0.59, CI 0.28-1.28) (Fig. 4).…”
Section: Mortalitymentioning
confidence: 92%
“…For acute lung injuries in humans, the therapeutic dose of sivelestat is 0.2 mg/kg/h. In the STRIVE clinical study, however, sivelestat was not effective 10) . This finding was different from tests carried out in Japanese patients with less severe acute lung injury, where the treatment was effective 8) .…”
Section: Effects Of Pmx And/or Sivelestat On Lps-induced Increases Inmentioning
confidence: 90%
“…In Japan, sivelestat has been widely used in clinical practice since 2002. However, in the United States and Europe, the effectiveness of sivelestat was not observed in the multi-center, double-blind, placebo-controlled trial (STRIVE study) 10) .…”
Section: Introductionmentioning
confidence: 99%
“…However, it would give an unbalanced view if we did not mention that many well-performed studies have failed to show any survival benefit of disease modifying agents, such as surfactant therapy [21], activated protein C [22], inhaled nitric oxide [23] and, more recently, b-agonists [24] and neutrophil elastase inhibitors [25] amongst others in ongoing studies. Several ongoing trials are on the horizon [26].…”
mentioning
confidence: 99%